Movimento da Reforma Sanitária e Movimento Sindical da Saúde do Trabalhador: um desencontro indesejado - Lacaz, Francisco Antonio De Castro; Reis, Ademar Arthur Chioro Dos; Lourenço, Edvânia Ângela De Souza [UNESP]; Goulart, Patrícia Martins; Trapé, Carla Andrea (Centro Brasileiro de Estudos de Saúde, 2020)
This article discusses the origin of the Brazilian Sanitary Reform Movement (MRSB) from the review of the literature published in the journal ‘Saúde em Debate’, by the National Commission on Sanitary Reform, from 1980 to 2010. (MSST), and how the fragile social base of the Health Reform is related to the ‘divorce’ between them. It shows the progress achieved by the MSST in the late 1970s and 1980s in the implementation of Worker’s Health Programs, which were carried out by the Unions advised by their inter-union body, in the struggle for health at work, an issue which was disregarded by MRSB. With the hegemony of global neoliberal productive restructure in the country and structural unemployment, there is a decline in the action of the Union movement, weakening its role in the struggle for health at work, which could have potentiated the fight for Brazilian Sanitary Reform.

O artigo discute a origem do Movimento da Reforma Sanitária Brasileira (MRSB) e do Movimento Sindical da Saúde do Trabalhador (MSST) e como a frágil base social da Reforma Sanitária tem relação com o ‘divórcio’ entre estes. Pauta-se na ótica da Saúde do Trabalhador a partir de revisão da literatura publicada na revista ‘Saúde em Debate’ e por autores nas décadas de 1980 a 2010 que compuseram a Comissão Nacional da Reforma Sanitária. Mostra o avanço obtido pelo MSST, nos anos 1970-1980, na implementação de Programas de Saúde do Trabalhador, protagonizados pelos sindicatos envolvidos na luta pela saúde no trabalho, assessorados por seu órgão intersindical, questão desconsiderada pelo MRSB. Com a hegemonia da reestruturação produtiva neoliberal global no País e o desemprego estrutural, há um declínio da ação do movimento sindical, enfraquecendo seu protagonismo na luta pela saúde no trabalho, o que poderia ter potencializado a luta pela Reforma Sanitária Brasileira.
Sanitary Reform Movement and Union Movement for Workers’ Health: an unwanted mismatch
Keywords: Health care reform; Labor unions; Occupational health; Unified Health System; Reforma dos serviços de saúde; Sindicatos; Saúde do trabalhador; Sistema Único de Saúde